The benefits of improving access to the United Kingdom rail network via the Access For All programme - Tony Duckenfield (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
"Access for All" is a United Kingdom government funded programme to make stations more accessible for people with disabilities by providing step free access along with complementary measures such as improved wayfinding information. Steer Davies Gleave was commissioned to evaluate the programme in a manner consistent with official guidance ("WebTAG"), and to quantify the benefits to rail passengers and train operators. This paper describes what data was collected, how it was collected, how it was analysed and what the results were. It also identifies some important lessons for improving the implementation of the programme, which may have wider applicability. In summary, the programme was shown to have a positive economic case even when only considering the narrow benefits included within WebTAG. Additional social and community benefits were also identified, and it was highlighted that better promotion of the programme would improve its value for money even further. While this particular case study focusses on United Kingdom rail stations, the lessons and methodological approach are applicable more widely.
Keywords: 330; Schienenpersonenverkehr; Verkehrsinfrastruktur; Räumliche Erreichbarkeit; Behindertenpolitik; Behinderte; Großbritannien